2021
DOI: 10.3390/ijms222312847
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Dual Transcriptional Analysis of Microalga Graesiella emersonii–Amoeboaphelidium protococcarum Pathosystem Uncovers Conserved Defense Response and Robust Pathogenicity

Abstract: The underlying mechanisms of microalgal host–pathogen interactions remain largely unknown. In this study, we applied physiological and simultaneous dual transcriptomic analysis to characterize the microalga Graesiella emersonii–Amoeboaphelidium protococcarum interaction. Three infection stages were determined according to infection rate and physiological features. Dual RNA-seq results showed that the genes expression of G. emersonii and A. protococcarum were strongly dynamically regulated during the infection.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
(49 reference statements)
1
2
0
Order By: Relevance
“…1 ), while fungal PGs peaked with 4 DPI and flatten until 7 DPI. The abundance of fungal PGs matches the reported reproduction cycle of A. protococcarum , which includes intrusion of host cells, phagocytosis of the host cytoplasm and maturation of spores within 3–5 DPI 32 , 34 .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…1 ), while fungal PGs peaked with 4 DPI and flatten until 7 DPI. The abundance of fungal PGs matches the reported reproduction cycle of A. protococcarum , which includes intrusion of host cells, phagocytosis of the host cytoplasm and maturation of spores within 3–5 DPI 32 , 34 .…”
Section: Discussionsupporting
confidence: 73%
“…The results included a predicted proteome, covering full life-cycle data including cellulases, which were likely involved in algal cell-wall penetration, and enzymes involved in chitin biosynthesis, indicating typical fungal metabolism. The responses and defense reactions to pathogen infection of A. protococcarum on the green microalga Graesiella emersonii have just recently been investigated 34 . The defense of G. emersonii included pattern recognition receptors, large heat shock proteins, and reactive oxygen scavenging enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of using such approaches to facilitate understanding the metabolic pathways required for fungal pathogenicity show that by comparative analysis of the genomes of the fungal pathogens and the oleaginous algal host Nannochloropsis oceanica , the differences in the key enzymes and genetic structure of the sterol biosynthetic pathway can be identified as targets for commercial fungicides [ 22 ]. And by transcriptomic analysis of the interaction processes between the microalga Graesiella emersonii and its endoparasite Amoeboaphelidium protococcarum, novel insights into robust pathogenicity of the parasite can be gained [ 14 ]. Recently, metabolomic analysis has demonstrated that the secondary metabolites, such as 3-hydroxyanthranilic acid and hordenine, can trigger the oxidative burst in H. pluvialis cells and can be used by P. sedebokerense to facilitate infection [ 69 ].…”
Section: Introductionmentioning
confidence: 99%